Strengthening the Quality of Work Life on Employee Performance through Competence and Organizations Citizenship Behaviour - Ipdwiyah Piting Purniawati; Mas’ud, Muchlis (Optima Science, 2023)
Employee performance plays an important role in the sustainability of the organization. The overall success of task responsibilities is largely determined by good human resources. The purpose of this research is to determine the quality of work life on the performance of employees with competence and organizational citizenship behavior. The number of samples in this study were sub-district employees in Pasuruan district, with a total of 97 employees as respondents. This research was conducted using Smart pls analysis with a quantitative method. The results of the study show that a good quality of work life can increase competence, if the indicators felt by employees can create a good quality of work life. (1) Good competence has not been able to improve employee performance, (2) competence has not been able to play a role in improving employee performance because employees have not been able to implement it. (3) Quality of work life is able to increase organizational citizenship behavior, (4) Organizational citizenship behavior is high which can contribute to employee performance, (5) Quality of work life is able to contribute to employee performance, (6) The effect of mediation has not been able to mediate relationships between quality of work life and performance, (7) Organizational citizenship behavior can play a role in mediating quality of work life and employee performance.